2022
DOI: 10.1002/capr.12590
|View full text |Cite
|
Sign up to set email alerts
|

Vocal indicators of facilitative interpersonal skills

Abstract: It has long been recognised that therapist reactions during difficult relational impasses with clients are implicated in psychotherapy outcomes and processes (Eubanks-Carter et al., 2015;Safran & Muran, 2000;Strupp & Binder, 1984). For example, Strupp (1997) noted that even highly experienced professional therapists had remarkable variation in how they responded to the most challenging situations with clients. Additionally, how therapists respond can significantly influence their clients (Henry et al., 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…One more recent study took a completely different approach to the assessment of FIS validity through acoustic analysis. Glasgow et al (2023) conducted the usual FIS ratings of therapist responses to the therapeutic situations, but then conducted acoustic analysis of fundamental frequency and spectral scope and range using audio recordings of 135 therapists involved in helping skills training. They found that fundamental frequency of the therapists’ voice recordings was indeed correlated with FIS ratings and that increased range was associated with higher FIS in women.…”
Section: Resultsmentioning
confidence: 99%
“…One more recent study took a completely different approach to the assessment of FIS validity through acoustic analysis. Glasgow et al (2023) conducted the usual FIS ratings of therapist responses to the therapeutic situations, but then conducted acoustic analysis of fundamental frequency and spectral scope and range using audio recordings of 135 therapists involved in helping skills training. They found that fundamental frequency of the therapists’ voice recordings was indeed correlated with FIS ratings and that increased range was associated with higher FIS in women.…”
Section: Resultsmentioning
confidence: 99%